Comparing Prospective Incident Severe Acute Respiratory Syndrome Coronavirus 2 Infection Rates During Successive Waves of Delta and Omicron in Johannesburg, South Africa. (16th December 2022) - Sokhela, Simiso; Bosch, Bronwyn; Hill, Andrew; Simmons, Bryony; Woods, Joana; Johnstone, Hilary; Madhi, Shabir; Qavi, Ambar; Ellis, Leah; Akpomiemie, Godspower; Bhaskar, Esther; Levi, Jacob; et al.
Abstract: In high-risk individuals in Johannesburg, during the Delta coronavirus disease 2019 wave, 22% (125/561) were positive, with 33% symptomatic (2 hospitalizations; 1 death). During Omicron, 56% (232/411) were infected, with 24% symptomatic (no hospitalizations or deaths). The remarkable speed of infection of Omicron over Delta poses challenges to conventional severe acute respiratory syndrome coronavirus 2 control measures. Abstract : Healthcare workers in Johannesburg were tested for SARS-CoV-2 virus and antibodies during the Delta and Omicron waves in 2021. Infection rates were higher in the Omicron wave (47%) versus the Delta wave (22%), but the infections were less severe with Omicron, with no hospitalisations required.